Patient With Severe Hyponatremia Caused by Adrenal Insufficiency Due to Ectopic Posterior Pituitary Lobe and Miscommunication Between Hypothalamus and Pituitary: A Case Report. Issue 10 (March 2016) - Grammatiki, Maria; Rapti, Eleni; Mousiolis, Athanasios C.; Yavropoulou, Maria; Karras, Spyridon; Tsona, Afroditi; Daniilidis, Michalis; Yovos, John; Kotsa, Kalliopi
Abstract : Abstract: Hyponatremia may be one of the clinical manifestations of adrenal insufficiency (AI) and during the diagnostic workup of hyponatremic patients investigation of AI should be included. We report the case of an 82-year-old patient who was admitted to our hospital with clinical symptoms and laboratory findings of hyponatremia. Following the diagnostic algorithm of hyponatremia we reached the diagnosis of AI. Clinician's attention must focus on the underlying cause of AI which in this case was hidden in a miscommunication between hypothalamus and pituitary due to an ectopic posterior pituitary lobe and became apparent by a pituitary magnetic resonance imaging (MRI) scan. Treatment with oral hydrocortisone resulted in full clinical recovery and electrolyte balance, which was maintained after 7 months of follow-up. Secondary AI is related with hyponatremia through increased ADH secretion. Although a hyponatremic episode may be the first presentation of AI, clinical suspicion is of high importance in order to place the right diagnosis. Disruption of communication between hypothalamus and pituitary is a rare but considerable cause of AI.